An investigation of the factors influencing food choices of mothers of children attending primary schools in the Metro North Education District of Western Cape Province, South Africa. - Smit, Yolande (Stellenbosch : Stellenbosch University, 2015)
Thesis (MNutr)--Stellenbosch University, 2015.